Photometric survey and taxonomic identifications of 92 near-Earth asteroids. (March 2018) - Lin, Chien-Hsien; Ip, Wing-Huen; Lin, Zhong-Yi; Cheng, Yu-Chi; Lin, Hsing-Wen; Chang, Chan-Kao
Abstract: A photometric survey of near-Earth asteroids (NEAs) was conducted from 2012 through 2014 at Lulin Observatory, Taiwan. The measurements of the color indices, B-V, V-R, and V-I allow the classification of 92 NEAs into seven taxonomic types. Of these samples, 39 of them are new classifications. The fractional abundances of these taxonomic complexes are: A ∼3%, C∼6.5%, D∼8%, Q∼26%, S∼37%, V∼6.5%, and X∼13%. This result is similar to that of Thomas et al. (2011) even though the populations of the D- and X-complex with low albedos are under-represented. The ratio of the C-cluster to the total population of S + C clusters are 0.22 ± 0.06 for H ≤ 17.0 and 0.31 ± 0.06 for H > 17.0, indicating a slightly higher fraction of dark-object population with sizes smaller than 1 km. Highlights: Only a small fraction of the near-Earth asteroids (NEAs) has been taxonomically classified. A photometric survey program is being carried out at Lulin Observatory, Taiwan. The first results of 92 NEAs observed between 2012 and 2014 are reported in this work.